2023
DOI: 10.1111/1759-7714.15009
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and its association with decreased risk of esophageal squamous cell carcinoma in betel nut chewers

Abstract: BackgroundBetel nut chewing involves the chewing of areca nuts or betel quid (areca nuts wrapped in betel leaves), which is associated with an increased risk of esophageal squamous cell carcinoma (ESCC). Statins have anticancer properties. We investigated the association between statin use and ESCC risk in betel nut chewers.MethodsThe study included 105 387 betel nut chewers matched statin users and nonusers. Statin use was defined as the use of ≥28 cumulative defined daily doses (cDDDs) of statin. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have indicated an association between statin use and a low risk of IS in HNC patients after RT. [42][43][44] A study indicated that oral antithrombotic therapy did not significantly mitigate the risk of IS. 45 In this study, we discovered that NPC patients with CAS and non-NPC patients with VAS were at elevated risks of IS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated an association between statin use and a low risk of IS in HNC patients after RT. [42][43][44] A study indicated that oral antithrombotic therapy did not significantly mitigate the risk of IS. 45 In this study, we discovered that NPC patients with CAS and non-NPC patients with VAS were at elevated risks of IS.…”
Section: Discussionmentioning
confidence: 99%